Seismic response of a highway bridge in case of vehicle-bridge dynamic interaction - Erdogan, Yildirim S.; Catbas, Necati F. (TECHNO-PRESS, 2020)
The vehicle-bridge interaction (VBI) analysis might be cumbersome and computationally expensive in bridge engineering due to the necessity of solving large number of coupled system of equations. However, VBI analysis can provide valuable insights into the dynamic behavior of highway bridges under specific loading conditions. Hence, this paper presents a numerical study on the dynamic behavior of a conventional highway bridge under strong near-field and far-field earthquake motions considering the VBI effects. A recursive substructuring method, which enables solving bridge and vehicle equations of motion separately and suitable to be adapted to general purpose finite element softwares, was used. A thorough analysis that provides valuable information about the effect of various traffic conditions, vehicle velocity, road roughness and effect of soil conditions under far-field and near-field strong earthquake motions has been presented. A real-life concrete highway bridge was chosen for numerical demonstrations. In addition, sprung mass models of vehicles consist of conventional truck and car models were created using physical and dynamic properties adopted from literature. Various scenarios, of which the results may help to highlight the different aspects of the dynamic response of concrete highway bridges under strong earthquakes, have been considered.
Keywords: vehicle-bridge interaction; recursive solution of coupled equation; far-field near-field earthquake motion; highway bridges; sprung-mass vehicle models; SOIL-STRUCTURE; NEAR-FAULT; FAR-FIELD; SYSTEM; PERFORMANCE; DAMAGE; Engineering